Investigation of kinase activation in fibrodysplasia ossificans progressiva - Sanvitale, CE (2014)
Fibrodysplasia ossificans progressiva (FOP) is a rare autosomal dominant disease resulting in episodic but progressive extraskeletal bone formation. FOP is caused by missense mutations in the cytoplasmic domain of the type I bone morphogenetic protein (BMP) receptor ACVR1, leading to dysregulated activation. Currently there are no available drug treatments and the structural mechanism of mutant activation is still poorly characterised. To address this, a number of BMP and TGFβ receptors, including FOP mutants of ACVR1 were cloned, expressed and purified for both structural and biophysical experiments. The arginine at the site of most recurrent FOP mutation, R206H, is common across all type I receptors except BMPR1A and BMPR1B which have a lysine at this site. The novel structure of BMPR1B differed to wild-type ACVR1 showing some of the conformational changes expected of the active conformation. However, a variety of disease related ACVR1 mutant structures, including ACVR1 R206H, revealed a surprisingly persistent inactive conformation in the kinase domain. Some conformational changes suggestive of activation were observed in the mutant Q207D affecting the ATP pocket, the β4–β5 hairpin and the activation loop. Additionally, the structure of the Q207E mutant showed a slight release of the regulatory glycine-serine rich domain from its inhibitory position. These subtle changes suggest that the mutant inactive conformation is destabilised and potentially more dynamic. In agreement, all of the ACVR1 mutants showed reduced binding to the inhibitory protein FKBP12. However, mutant phosphorylation of the substrate Smad1 was not constitutive, but dependent on the co-expression of the partner ACVR2, consistent with recent evidence from transgenic knock-out mice. A novel 2-aminopyridine inhibitor scaffold with favourable specificity for ACVR1 was identified using a fluorescence-based thermal shift assay. Further derivatives were characterised with improved potency and selectivity. The crystal structures of ACVR1 bound to these inhibitors showed exquisite shape complementarity, contributing to their favourable specificity. This work has increased the understanding of FOP-associated mutant activation and provided a novel starting scaffold for potential drug development.